2018
DOI: 10.18632/oncotarget.24045
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of mitochondrial function and mTOR pathway as a therapeutic strategy for diffuse intrinsic pontine glioma

Abstract: Diffuse Intrinsic Pontine Gliomas (DIPG) are the most devastating of all pediatric brain tumors. They mostly affect young children and, as there are no effective treatments, almost all patients with DIPG will die of their tumor within 12 months of diagnosis. A key feature of this devastating tumor is its intrinsic resistance to all clinically available therapies. It has been shown that glioma development is associated with metabolic reprogramming, redox state disruption and resistance to apoptotic pathways. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…This encouraged us to explore PENAO in this combination. We demonstrated that HOS cells displayed a reasonable inhibition in mitochondrial activity (decreased OCR) after PENAO single agent treatment, which was similarly observed in glioblastoma and diffuse intrinsic pontine glioma [50,52,71,72]. Our results also showed a significant reduction of OCR and increase of ECAR in HOS cells treated with PENAO plus gefitinib when compared to single agents.…”
Section: Discussionsupporting
confidence: 78%
“…This encouraged us to explore PENAO in this combination. We demonstrated that HOS cells displayed a reasonable inhibition in mitochondrial activity (decreased OCR) after PENAO single agent treatment, which was similarly observed in glioblastoma and diffuse intrinsic pontine glioma [50,52,71,72]. Our results also showed a significant reduction of OCR and increase of ECAR in HOS cells treated with PENAO plus gefitinib when compared to single agents.…”
Section: Discussionsupporting
confidence: 78%
“…[]). These mutations invariably drive intracellular oxidative stress cascades that damage lipids, proteins, and DNA, contributing to genome instability, clonal evolution, and treatment resistance (reviewed in ref. []).…”
Section: Introductionmentioning
confidence: 99%
“…Co-administered with perifosine (an AKT inhibitor), temsirolimus has shown antiproliferative and anti-apoptotic effects independently of the PTEN status, related to an inhibition in the PI3K/AKT/mTOR pathway [271]. The inhibition of mTOR by temsirolimus increases the cytotoxic and pro-apoptotic activity of PENAO (an inhibitor of adenine nucleotide translocase) on DIPG (diffuse intrinsic pontine gliomas) cells through the generation of reactive oxygen species, ATP depletion, and an increase in the activity of AMPK, with the subsequent inhibition of the PDGFRa /PI3K/mTOR and HSP90 signaling pathways [272]. Chandrika et al demonstrated that mTOR inhibitors like temsirolimus and torin significantly reduce the expression levels of mesenchymal markers (fibronectin, vimentin, and YKL40) and neural stem cell markers (Sox2, Oct4, nestin, and mushashi1) induced by the tumor promoter phorbol-myristate-acetate in LN-18 glioma cells, through the dephosphorylation of the transcriptional factor STAT3 [273].…”
Section: Introductionmentioning
confidence: 99%